Ամենայն Հայոց Մեծ Վեհափառը (Յուշեր) - Աւագեան, Ծովակ (Տպարան Սրբոյ Յակոբեանց)
Վազգէն Ա. Վեհափառի մասին։
Keywords: Auxiliary Sciences of History; Biography; Christianity; History of the Armenian Church